(untitled) (Development Service Industry Management, 2024)
The purpose of the article is to study the planning of the company’s activities as a tool of the economic component of the concept of sustainable development, followed by the formation of effective proposals aimed at integration into the business strategy in order to reduce risks. The economic component of sustainable development implies that the enterprise should not only achieve financial benefit, but also do so in an ecologically responsible manner. This includes the introduction of energy-efficient technologies, reduction of emissions of harmful substances and rational use of natural resources. It is shown that planning activities in this context helps the enterprise to integrate environmental criteria into business strategies, which helps to reduce the negative impact on the environment and improves the image of the company. It is noted that social responsibility is also an integral part of sustainable development. Businesses must take into account the interests of employees, consumers and local communities. Planning socially responsible initiatives helps to increase consumer loyalty, attract qualified employees and improve relations with society. The key components of planning, the economic component and the principles of sustainable development are considered. On the basis of meaningful components, a scheme of integration of activity planning into the economic component of sustainable development of the enterprise was built. It was determined that the main aspects of planning activities within the framework of sustainable development are: assessment of the current state and analysis of the environment, establishment of goals and performance indicators, development of strategy and action plan, implementation and monitoring, evaluation of results and reporting It was established that activity planning is a key tool of the economic component of the concept of sustainable development of the enterprise. It allows enterprises to effectively manage resources, reduce risks, integrate environmental and social criteria into business strategies and implement innovations. This contributes to the achievement of long-term stability and success, which is the basis for sustainable development in modern conditions.